2018
DOI: 10.1093/mnras/sty1168
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the radial abundance gradients of nitrogen and oxygen of the Milky Way

Abstract: We present spectra obtained with the 10.4 m Gran Telescopio Canarias telescope of 13 Galactic H ii regions, most of them of very low ionisation degree. The objects are located along the Galactic disc, with R G from 5.7 to 16.1 kpc. We determine T e ([N ii]) for all of them. We obtain -for the first time -a radial abundance gradient of N that is independent on the ionisation correction factor. The radial distribution of the N/O ratio is almost flat, indicating that the bulk of N is not formed by standard second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
81
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 84 publications
16
81
3
Order By: Relevance
“…This scatter is generally smaller than the amplitude of the radial variation, which typically ranges from 0.1 to 0.3 dex over the radial range we observe. It has been previously shown that strong line methods systematically produce smaller scatter in their radial gradients than direct temperature methods (Arellano-Córdova et al 2016), but this very small systematic scatter with respect to the radial gradient is similar to what has been found using direct temperature methods to measure the metallicity in the Milky Way (Esteban & García-Rojas 2018). It is, however, much smaller than what has been found with direct temperature methods for three nearby galaxies by the CHAOS project (∼0.1 dex; Croxall et al 2015;Berg et al 2015;Croxall et al 2016) and in M33 (0.11 dex; Rosolowsky & Simon 2008).…”
Section: Subtle Evidence For Azimuthal Variationssupporting
confidence: 72%
“…This scatter is generally smaller than the amplitude of the radial variation, which typically ranges from 0.1 to 0.3 dex over the radial range we observe. It has been previously shown that strong line methods systematically produce smaller scatter in their radial gradients than direct temperature methods (Arellano-Córdova et al 2016), but this very small systematic scatter with respect to the radial gradient is similar to what has been found using direct temperature methods to measure the metallicity in the Milky Way (Esteban & García-Rojas 2018). It is, however, much smaller than what has been found with direct temperature methods for three nearby galaxies by the CHAOS project (∼0.1 dex; Croxall et al 2015;Berg et al 2015;Croxall et al 2016) and in M33 (0.11 dex; Rosolowsky & Simon 2008).…”
Section: Subtle Evidence For Azimuthal Variationssupporting
confidence: 72%
“…Therefore, the presence of a flat N/O versus O/H relation in a galactic disc has a difficult and non-unique explanation. In their paper about the N and O abundance gradients in the Milky Way, Esteban & García-Rojas (2018) pointed out that the constant N/O ratio would indicate that the bulk of N should have a primary origin, and this would be also the situation in M31. Hydrodynamical cosmological simulations of galaxies by Vincenzo & Kobayashi (2018) using the stellar yield set by Kobayashi et al (2011) find almost flat trends in N/O versus O/H diagrams when ignoring the contribution of failed supernovae.…”
Section: About the Normalization Of Radial Gradientsmentioning
confidence: 99%
“…We also assume a nitrogen abundance relative to hydrogen, X N , from the fit as a function of Galactocentric distance (in kpc) presented by Esteban & García-Rojas (2018), The distance to the Galactic center R gal for a given velocity component with Galactic longitude l, latitude b, and local standard of rest (LSR) velocity V LSR , is given by…”
Section: Hydrogen Recombination Line Emissionmentioning
confidence: 99%
“…The typical scatter in the electron temperature found by Quireza et al (2006) is about ±350 K and results in a typical 13% uncertainty in the derived electron density. The typical scatter from the fit to X N as a function of Galactocentric distance presented by Esteban & García-Rojas (2018), is about 23%, resulting in a typical 44% uncertainty in the derived electron density. We estimated the uncertainty in the [N II]/RRL ratio by propagating those of the integrated intensities of the [N II] and RRL lines.…”
Section: Uncertaintiesmentioning
confidence: 99%